P53 expression in ischemic rat models after the administration of ketamine and ketamine-xylazine - Ety Sari Handayani; Zainuri Sabta Nugraha; Kuswati Kuswati; Muhammad Yusuf Hisyam; Untung Widodo; Nurul Hidayah; Sahdella Sahdella; Wimpy Wimpy (Universitas Ahmad Dahlan, 2020)
Ketamine and ketamine-xylazine are often used as anesthetic drugs in animal models of ischemia. However, their neuroprotective and neurotoxic effects in ischemic animal models that have undergone tBCCAO are still under debate. The protein p53 is a pro-apoptotic factor involved in the cellular mechanism of ischemia. The interaction between death-associated protein kinase 1 (DAPK 1) and p53 is fundamental in determining whether cells experience necrosis or apoptosis in an ischemic stroke. This study was purposed to identify the presence or absence of differences between the p53 expressions in the brains of tBCCAO-induced ischemic rat models after the administration of ketamine and ketamine-xylazine. It employed a post-test control group design with four groups of adult male Wistar rats as the subject: (1) sham group operated with ketamine, (2) sham group operated with ketamine-xylazine, (3) models of tBCCAO-induced ischemia with ketamine, and (4) models of tBCCAO-induced ischemia with ketamine-xylazine. Ketamine was administered at the dose of 75mg/kg BW, while xylazine was at 8 mg/kg BW. The expression of p53 in rat brains was assessed by semi-quantification, specifically IHC staining with anti-p53 antibodies. P53 expression appeared as brownish stains in the cytoplasm of forebrain pyramidal neurons, and in this study, it was measured using the Allred score. The ANOVA test yielded a p-value of >0.05, implying the absence of difference between the p53 expressions in the brains of tBCCAO-induced ischemic rat models receiving ketamine and ketamine-xylazine.